ArtAura

Location:HOME > Art > content

Art

Proving a_n^m ≡ -1 mod n

January 11, 2025Art3450
Proving a_n^m ≡ -1 mod n In this article, we will provide a detailed p

Proving a_n^m ≡ -1 mod n

In this article, we will provide a detailed proof of the statement that for all n ≥ 2 and m ≥ 1: [a_n^m] ≡ -1 mod n, where a_n n√(n^2 - n) and the brackets denote rounding down to the nearest integer (floor function).

Introduction and Problem Statement

Given the sequence a_n n√(n^2 - n), our goal is to show that for all integers n ≥ 2 and m ≥ 1:

[a_n^m] ≡ -1 mod n,

where the notation [-] indicates rounding down to the nearest integer (floor function).

Step-by-Step Proof

First, we will deal with the base case where m 1:

We need to prove:

?a_n? ≡ -1 mod n, or equivalently ?n√(n^2 - n)? ≡ -1 mod n.

We start by analyzing the expression n^2 - n:

Note that:

n - 1^2 ≤ n^2 - n (n - 0.5)^2.

Since n^2 - n (n - 0.5)^2 - 0.25,

we can write:

n - 1 n√(n^2 - n) n - 0.5.

The floor of n√(n^2 - n) is therefore:

?a_n? n - 1.

It's straightforward to see that:

n - 1 ≡ -1 mod n.

This completes the base case for m 1.

Extending to Higher Powers

For m ≥ 2, directly proving ?a_n^m? ≡ -1 mod n is not advisable. Instead, we will analyze the related sequences:

Defining Sequences and B_n

Define:

a_n n√(n^2 - n)

b_n n - √(n^2 - n)

These sequences have the following properties:

a_n b_n n

a_n b_n 2n

Since both a_n and b_n are congruent to 0 modulo n:

a_n b_n^k ≡ 0 mod n

b_n a_n^k ≡ 0 mod n

Induction Step

We will use induction to prove the congruence:

?a_n^m b_n^m? ≡ ?a_n^{m-2} b_n^{m-1}? mod n

For small values of m, let's check:

a_n b_n^2 a_n^2 b_n^2 b_n a_n^2 2a_n b_n a_n b_n^3 a_n^3 b_n^3 b_n a_n^3 3a_n b_n^2 a_n b_n^4 a_n^4 b_n^4 b_n a_n^4 4a_n^2 b_n^2

These relations show that the induction step can be established, and thus:

?a_n^{m-2} b_n^{m-1}? ≡ -1 mod n

Analyzing 1/2 b_n ≤ 2 - √2

Since b_n is positive and small:

1/2 ≤ b_n 2 - √2 ≈ 0.59

This inequality will be crucial in the following steps. We can analyze the product:

tn - 1 a_n^m tn

leading to:

?a_n^m? tn - 1

Since:

tn - 1 ≡ -1 mod n

This completes the proof for all m ≥ 1.

Conclusion

We have shown that for all n ≥ 2 and m ≥ 1:

?a_n^m? ≡ -1 mod n

Using detailed steps and properties of the floor function and congruences, this proof is both rigorous and comprehensive.